Anthelminthic potential of Phytolaccadodecandra and Albizia antihelminticain calves - Tumwesigye, Wycliffe; Murokore, Justus; Isharaza, William; Lejju, B. Julius; Safari, David; Adiukwu, B. Paul (Journal of Scientific and Innovative Research, 2015)
Using herbal de-wormers in livestock has attracted much research attention in the recent past. Considerable research has been done in developed countries but there is paucity of information in Sub Sahara Africa (SSA) countries including Uganda. This study aimed at establishing the potential of Phytolaccadodecandra (pd) and Albizia antihelmintica (zia) on reducing egg count per gram (EPG) for Fasciola, Strongyles and Monezia species in calves. Body weights of seventy six calves purposefully selected from 5 farms were measured. Twenty six calves were treated with pd, 24 with zia and 26 with Albendazole 10% (zole) as a control. The calves were left to graze in their respective farms in controlled paddocks. Single dose treatment was given to each calf and rectal samples were collected after every week for a period of four weeks. The samples were preserved in 10% formal saline and EPG analysis was done using Telemman’s sedimentation method. Both the numbers and types of gastrointestinal worms eggs present in the dung of calves were determined before and after drug administration. Results show significant differences in Fasciola EPGfor calves treated with Albendazole 10% and those treated with pd (p = .044); Strongyles EPG for calves treated with Albendazole 10% and those treated with zia (p = .007). No significant differences were observed in Monezia EPG for the three treatments used. This suggests that Albendazole 10% is more effective than zia and pd on Fasciola, Strongyles and Monezia species while pd and zia extracts have almost the same effectiveness on all the three species of parasites studied.
Keywords: Phytolaccadodecandra; Albizia antihelmintica; Albendazole; Fasciola; Strongyles; Monezia